Prognostic value of right atrial pressure‐corrected cardiac power index in cardiogenic shock. (11th August 2022) - Baldetti, Luca; Pagnesi, Matteo; Gallone, Guglielmo; Barone, Giuseppe; Fierro, Nicolai; Calvo, Francesco; Gramegna, Mario; Pazzanese, Vittorio; Venuti, Angela; Sacchi, Stefania; De Ferrari, Gaetano Maria; Burkhoff, Daniel; et al.
Abstract: Aim: The pulmonary artery catheter (PAC)‐derived cardiac power index (CPI) has been found of prognostic value in cardiogenic shock (CS) patients. The original CPI equation included the right atrial pressure (RAP), accounting for heart filling pressure as a determinant of systolic myocardial work, but this term was subsequently omitted. We hypothesized that the original CPI formula (CPIRAP ) is superior to current CPI for risk stratification in CS. Methods and results: A single‐centre cohort of 80 consecutive Society for Cardiovascular Angiography and Interventions (SCAI) B‐D CS patients with available PAC records was included. Overall in‐hospital mortality was 21.3%. Results showed CPIRAP to be the strongest haemodynamic predictor of in‐hospital death ( p adj = 0.038), outperforming CPI [area under the receiver operating characteristic (ROC) curves: 0.726 and 0.673, P ‐for‐difference = 0.025]. When the population was stratified according to the identified CPIRAP (0.28 W/m 2 ) and accepted CPI (0.32 W/m 2 ) thresholds, the cohort with discordant indexes (low CPIRAP and high CPI) comprised a group of 13 patients featuring a congested phenotype with frequent right ventricle or biventricular involvement. In this group, in‐hospital mortality was high (30.8%) similar to those with concordant low CPI and CPIRAP . Conclusion: Incorporating RAP in CPI calculation (CPIRAP ) improves the prognostic yield in patients with CS SCAI B‐D. A cut‐off of 0.28 W/m 2 identifies patients at higher risk of in‐hospital mortality. The improved prognostic value of CPIRAP may derive from identification of patients with more intravascular congestion who may experience substantial in‐hospital mortality, uncaptured by the commonly used CPI equation.